Use of Point-of-Care Ultrasound for Early Identification of Acute Aortic Root Dissection - Kristina Thomas; Omar Amr (Case Reports in Critical Care)
Point-of-care ultrasound (POCUS) is becoming a frequently utilized imaging tool in the emergency department (ED) as it can aid in early diagnosis of many pathologies. This is a case report of a 55-year-old male who presented to the emergency department by ambulance for sudden onset chest pain followed by a syncopal episode. Point-of-care echocardiogram revealed a large pericardial effusion with a significantly dilated aortic root, concerning for aortic dissection. Patient was emergently taken for a computed tomography (CT) scan, which was only remarkable for an ascending thoracic aortic aneurysm but failed to show an aortic dissection flap. On repeat POCUS, a dissection intimal flap, large pericardial effusion with tamponade physiology, and aortic regurgitation were identified and later confirmed on transesophageal echocardiogram. This case report details a rare pathology that was correctly identified on initial POCUS before it was seen on CT scan.